Pengaruh Kualitas Pelayanan Harga dan Lokasi Terhadap Kepuasan Konsumen DM Parcel - Iskandar Ali Alam; Balqis Ananda Zahra (Jurnal EMT KITA, 2023)
The rapid development of the business world during the COVID-19 pandemic, especially in the service sector, has had a positive impact on DM Parcel, a Sultan Agung Street No. 52 Kedaton Bandar Lampung and was established in 2018. The company has an organizational structure of 1 owner and 4 employees, and implements a corporate culture that emphasizes creativity, service, and innovation. customer satisfaction. This study focuses on the influence of three factors, service quality (X1), price (X2) and location (X3) on customer satisfaction (Y). The analytical method used is quantitative analysis. The results of data analysis show that service quality has a significant influence on customer satisfaction with DM Parcel. However, price and location did not have a significant effect on customer satisfaction. In addition, it was found that there is a significant influence between service quality, price, and location on DM Parcel customer satisfaction. This finding could be a benchmark for DM Parcel in improving its marketing and service strategies to increase customer satisfaction. Furthermore, this study also contributes to understanding the factors affecting consumer satisfaction in the service industry during the COVID-19 pandemic.